Kualitas Pelayanan Publik Dalam Pembuatan KTP Elektronik Di Kecamatan Banjar Kabupaten Pandeglang - Anisa Anisa; Ibanez Nugraha (Institut Nalanda, 2024)
The government plays an important role in providing good public services for all its residents. To support the government's role in providing public services, efforts to improve service quality are carried out consistently by taking into account the needs and expectations of the community. This research was conducted to determine the quality of electronic identity cards (E-KTP) in Banjar sub-district, Pandeglang district. The dimensions of service quality used consist of constraints, responsiveness, assurance, empathy and physical evidence. With a qualitative approach. This research was carried out at the Banjar sub-district office. Data collection and collection was carried out through observation and interviews as a result of this research to show that indicators of service quality and convenience indicate good conditions or lack of service quality. Meanwhile, the responsibility, comfort and complete facilities indicators need to be improved or have entered an unsatisfactory condition.